Applying a fuzzy trust model to e-commerce systems - Chang, Elizabeth; Schmidt, S.; Steele, R.; Dillon, Tharam S. (Springer-Verlag, 2005)
Moving towards automated service selection, contract negotiation, and contract fulfilment remains a promising vision for E-commerce systems. Trust is one of the main reasons why this vision is not put into practice in current E-commerce systems. Various theoretical models and technical concepts are in place to facilitate crucial factors such as system interoperability or communication-level security. However, proven models, to measure social values such as trustworthiness, reputation or credibility of service consumers and service providers in loosely coupled, distributed E-commerce systems, are the missing factors which prevent the adoption of automated service interaction. This paper demonstrates the application of our Fuzzy trust model in an Ecommerce platform. We apply an exemplary business scenario to demonstrate the usage of our Fuzzy trust model.